The etiologic, microbiologic, clinical and outcome characteristics of immunocompetent young children <2 years of age hospitalized with acute neutropenia - Dov Tschernin; Yariv Fruchtman; Ruslan Sergienko; Odeya David; Ron Leibovitz; Julia Mazar; Eugene Leibovitz (Pediatrics and Neonatology)
Background: To describe the etiologic, microbiologic, clinical and outcome characteristics of acute neutropenia (absolute neutrophil count, ANC, <1.5 × 109/L) in hospitalized immunocompetent children. Methods: Serious bacterial infections (SBI) were defined as culture-positive blood, urine, cerebrospinal fluid, articular fluid or stool infections, alveolar pneumonia, Brucellosis and Rickettsiosis. Results: 431/671 (64.2%) healthy infants and children hospitalized with acute neutropenia were <2 years of age; 176 (40.8%), 167 (38.8%) and 88 (20.4%) patients were aged 0–3, 4–12 and 13–24 months, respectively. There were 19 (4.4%), 53 (12.3%), 140 (32.5%) and 209 (50.8%) patients with ANC count <200, 200–500, 501–1000 and 1001–1500 × 109 cells/L, respectively. Severe neutropenia (<500 × 109/L) was recorded in 72 (16.7%) patients. Fever >38 °C was present in 208/431 (48.3%) patients. Blood cultures were positive in 10 (2.3%), with Brucella melitensis, Staphylococcus aureus and Enterobacter spp. identified in 4, 3 and 2 patients, respectively; 5/10 patients with positive blood cultures were <3 months of age. Overall, 55/431 (12.7%) and 65/431 (15.1%) patients were diagnosed with SBIs and bacterial infections, respectively. Nasal washings-PCR for respiratory viruses was positive in 139/293 (47.4%) patients tested. An infectious etiology (bacterial and/or viral) was diagnosed in 190/431 (44.1%) patients. Three patients were diagnosed with acute lymphocytic leukemia. Resolution of neutropenia was achieved in 111/208 (53.4%) evaluable patients (63%, 50.6% and 48% of patients aged 0–3, 4–12 and >12 months, respectively and 56.8%, 53.5% and 52% of patients with severe, moderate and mild neutropenia, respectively). Conclusion: Acute neutropenia is common in immunocompetent children <2 years of age and is frequently associated with viral infections. We showed a substantial involvement of bacterial infections and particularly SBIs in the etiology of acute neutropenia. After a 1-month follow-up, resolution of neutropenia occurred in half of the patients, without association with age subgroups and with neutropenia severity.